Impact of digital transformation on HR in a corporate world - Maheen, Saarina (2020)
The main objective of this thesis is to analyze the importance of digital transformation in the corporate world and understand how it is affecting HRM in creating a sustainable business. Furthermore, the study involves identification of problems created by the digital transformation in the workplace and comes up with potential solutions to these problems. This theoretical analysis is also put into practical approach by carrying out case studies on two global companies that are namely: Huawei Investment and Holding Co., Ltd and EY Co. Ltd; one of which is known for technological operations and the other for business service providers. Finally, a conclusion is drawn by comparing the impact of digital transformation on the two companies with completely different operational sectors.